The Production Technology of Traditional Pottery Terenang in Temin Kraf = Teknologi Penghasilan Tembikar Tradisional Terenang di Temin Kraf - Mohd Zamani, Nor Peah; Muhammad Nubli, Abdul Wahab; Hamdzun, Haron (Pnerbit UPSI, 2017)
Terenang is one of the local traditional earthenware products in Peninsular Malaysia other than Labu Sayong and Mambong pottery. Terenang production activities centered in Kampung Pasir Durian and Temin Kraf in Jerantut, Pahang. Along with the modern advancement, the manufacturing of traditional pottery is also experiencing changes in terms of technology usage as demonstrated through the Labu Sayong’s production in Perak. The use of modern technology in the manufacturing process is very helpful in preserving the activity of extinction in development. However, the question is whether the Terenang pottery production activity uses the same modern technology during the distribution process. This research uses qualitative research approach that captures descriptively through observation, interview and document analysis towards the Terenang production process at Temin Kraf. The results showed that the use of modern technology in the manufacture of traditional pottery craft Terenang at Temin Kraf. This can be observed in the process of primary materials, the manufacturing process, the decor, and the combustion method. Temin Kraf’s effort in utilizing the use of modern technology is a step that brings this pottery activity to another new level that can diversify the types and designs of Terenang as well as being able to increase the distribution amount immediately. However, this study suggests the need for a proactive and drastic efforts taken by the government toensure that this legacy will continue to be preserved in order to be appreciated by future generations.